1989
DOI: 10.1002/yea.320050304
|View full text |Cite
|
Sign up to set email alerts
|

Structure and nuclear localization signal of the SK13 antiviral protein of Saccharomyces cerevisiae

Abstract: The yeast chromosomal genes SKI2, SKI3, SKI4, SKI6, SKI7 and SKI8 repress the replication of double-stranded RNA viruses, protecting the host from the otherwise lethal effects of the virus. We cloned and sequenced the SKI3 gene and found that it encodes a 163 kDa protein including a typical nuclear localization signal. Cell fractionation experiments show that the SKI3 gene product is indeed tightly associated with nuclei and that the putative nuclear localization sequence directs beta-galactosidase into the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 35 publications
(18 reference statements)
1
37
1
Order By: Relevance
“…We have shown by two independent means that Ski2p and Ski3p are cytoplasmic+ This is contrary to expectations based on human Ski2w (Qu et al+, 1998) and to previously published results for Ski3p (Rhee et al+, 1989)+ In addition Ski2p contains two putative overlapping canonical bipartite nuclear localization signals (NLSs)+ Mutation of amino acids 622-624 (arginine-lysine-arginine) to three alanines deletes a cluster of basic residues that simultaneously disrupts both NLSs+ This mutant complemented an xrn1 ski2 double mutant (J+T+ Brown & A+W+ Johnson, unpubl+ observation), indicating that the putative NLSs were not important with respect to Xrn1p activity+ Previous work on Ski3p demonstrated cofractionation of Ski3p-LacZ with nuclei on Percoll gradients+ We noted in our indirect immunofluorescence experiments that the signal for Ski3p was most intense around the nucleus+ Thus the nuclear cofractionation of Ski3p-LacZ observed previously may have reflected a loose association of Ski3p with material surrounding the nucleus+ Our results suggest that there are significant differences between the human and yeast Ski2 proteins+ The human protein, Ski2w, is primarily localized to the nucleolus, the site of ribosome biogenesis (Qu et al+, 1998), with a smaller amount of the protein thought to be bound to ribosomal 40S subunits in the cytoplasm+ We examined the sedimentation of yeast Ski2p on sucrose gradients and found that the protein sedimented throughout sucrose gradients (including polysomal fractions) but was not consistent with ribosomal association (X+ Bai and A+W+ Johnson, unpubl+ observation)+ It is possible that an additional SKI2 homolog exists in humans that is more similar in function to yeast SKI2+ Alternatively the human protein may have gained additional functions+…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We have shown by two independent means that Ski2p and Ski3p are cytoplasmic+ This is contrary to expectations based on human Ski2w (Qu et al+, 1998) and to previously published results for Ski3p (Rhee et al+, 1989)+ In addition Ski2p contains two putative overlapping canonical bipartite nuclear localization signals (NLSs)+ Mutation of amino acids 622-624 (arginine-lysine-arginine) to three alanines deletes a cluster of basic residues that simultaneously disrupts both NLSs+ This mutant complemented an xrn1 ski2 double mutant (J+T+ Brown & A+W+ Johnson, unpubl+ observation), indicating that the putative NLSs were not important with respect to Xrn1p activity+ Previous work on Ski3p demonstrated cofractionation of Ski3p-LacZ with nuclei on Percoll gradients+ We noted in our indirect immunofluorescence experiments that the signal for Ski3p was most intense around the nucleus+ Thus the nuclear cofractionation of Ski3p-LacZ observed previously may have reflected a loose association of Ski3p with material surrounding the nucleus+ Our results suggest that there are significant differences between the human and yeast Ski2 proteins+ The human protein, Ski2w, is primarily localized to the nucleolus, the site of ribosome biogenesis (Qu et al+, 1998), with a smaller amount of the protein thought to be bound to ribosomal 40S subunits in the cytoplasm+ We examined the sedimentation of yeast Ski2p on sucrose gradients and found that the protein sedimented throughout sucrose gradients (including polysomal fractions) but was not consistent with ribosomal association (X+ Bai and A+W+ Johnson, unpubl+ observation)+ It is possible that an additional SKI2 homolog exists in humans that is more similar in function to yeast SKI2+ Alternatively the human protein may have gained additional functions+…”
Section: Discussioncontrasting
confidence: 99%
“…The current models for Ski protein function make certain predictions about their localization+ A role in 39 mRNA degradation would be supported by a cytoplasmic localization and a role in ribosome biogenesis would be supported by a nuclear or nucleolar localization+ In an effort to dissect the general cellular role of the antiviral Ski proteins, we examined the protein interactions of Ski2p, Ski3, and Ski8p and the intracellular localization of Ski2p and Ski3p+ Ski3p is a 164-kDa protein that contains ten copies of a tetratricopeptide repeat (TPR) (Rhee et al+, 1989)+ TPR proteins are typically found in protein complexes and often in association with WDrepeat proteins (Goebl & Yanagida, 1991;van der Voorn & Ploegh, 1992;Neer et al+, 1994;Smith et al+, 1999)+ Ski3p also contains a canonical leucine zipper motif (LX 6 LX 6 LX 6 L) from amino acid residues 1232 to 1253 (J+T+ Brown & A+W+ Johnson, unpubl+ observation), suggesting protein oligomerization+ Ski3p in yeast is reported to be nuclear (Rhee et al+, 1989)+ Ski8p is a 44-kDa protein containing five WD repeats (Matsumoto et al+, 1993;Smith et al+, 1999; "The WD-repeat Family of Proteins" at http://bmerc-www+bu+edu/wdrepeat/)+ Based on the similarity of phenotypes of ski3 and ski8 mutants and the protein families to which these proteins belong, it has been suggested that these proteins physically interact (Matsumoto et al+, 1993;Masison et al+, 1995 Figure 1A were not specific to tagged Ski2p+ Quantitation of the Ski2p and putative Ski3p and Ski8p bands indicated that they were present in a 1:1:1 stoichiometry when accounting for the number of methionines in each species+ We repeated this immunoprecipitation experiment in ski3 and ski8 deletion mutants+ Coimmunoprecipitation of Ski2p in a SKI3 deletion mutant abolished the coprecipitating band migrating in the position expected for Ski3p (Fig+ 1A, ski3⌬ )+ Surprisingly, deletion of SKI3 also abolished the putative Ski8p band+ Similarly, in a SKI8 deletion mutant, the putative Ski3p and Ski8p bands were both absent (Fig+ 1A, ski8⌬ )+ Similar immunoprecipitation experiments performed in ski6-2, ski4-1, and ski7::HIS3 strains showed no effect of these mutations on the Ski2p complex (Fig+ 1A, ski6, and data not shown)+ These results strongly suggest that Ski2p is in a complex with Ski3p and Ski8p and that the interaction of Ski2p with Ski3p and Ski8p requires Ski8p and Ski3p, respectively+ Upon overexposure of the autoradiograph shown in Figure 1A or in additional immunoprecipitation experiments, we did not observe additional proteins coprecipitating specifically with Ski2p+…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One plausible explanation for the apparent absence of covalently attached caps to purified virus is that this interaction is deleterious to the host and therefore is prevented from occurring in the cell. The presence of the known dsRNA yeast viruses does not represent a severe handicap for the host, because the virus copy number (typically 1,000 L-A, 100 L-BC, and 150 M1 per cell [56]) is curtailed by a class of cellular genes termed SKI (superkiller [39,40,50,57,58]). An intriguing possibility is that the product of one or more of the SKI genes prevents the interaction between the virus coat protein and the cap structure of cellular mRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…The initial 100 amino acids were found to have a net charge of + 10, while residues 12 to 61 had a net charge of +14. Residues 51 to 60, RTLKTKFRRL, exhibited some similarity to a nuclear localization signal (20,21,27). A serine-rich (31%) region was observed between residues 100 and 150, with a string of serine resdues (9 GTT GAT GAC CGA ATG CAT TGG TTC ACT GAT TCA GAT GTG GAA GAA CAA TCG CAL -1850* -1830* -1810* TCT TAT AAA GGT GAC CTG CGG AAA TTT TTC TGC CAT GGA CCT TAA GTA ACA TTC AAC CTG -1790* -1770* -1750* GCC CCA TAC TTG CGG ATG TGA GTG TAT TAT GAC TTC TTC AAA ATT TCC AAG GGA TGC AAT -1730* -1710* -1690* ACC ATT TGG TAG TTG GAT TGG GCT GAT TAG ACA ATG GGT ALT GGG TAC ATA TTG CAC CGC -1670* -1650* -1630* TAT AAC TTC TAT ATC TGG CGT AAT TCT ATT AGT ATC TGC TGG AGC AGG TAA GCA TAG GGC - (M1682-19b) and da182 mutant (MO2) strains with plasmids that contained the DAL7 UAS (plasmid pHY129), the UAS and URS (plasmid pHY135), or all three elements (plasmid pHY174).…”
Section: Resultsmentioning
confidence: 99%